(3cJGH MPa ef fSH bQjTis - (3eDQL Hf YeQh Hf GdMGQK, CHh ajO,J (B195 (3g` s ((3GHQGgje Hf YHO Gddg Hf eMeO GdMQHi GdhQGb s)
(3ChdgG (B:s
(3MOKfi CHh LYaQ CMeO Hf eMeO GdjRjOi , Yei , bGd (B: (3CNHQfG CHh ajO GdSOhSi bGd (B: (3gPG cJGH MPa ef GdfSH s
(3BNQgG (B:s
(3ef bhd fGaY Hf YHO efGa Hf hgjH (B: (3GYGJHce MJi GdeeGJ hhOce efhW dOi GdLhRGA Ch gh CbQH s
(3QhGjI CHj YHO Gddg eMeO Hf GdYHGS GdjRjOis
(3Yf Yeg CHj LYaQ CMeO Hf eMeO GdjRjOi Yf eDQNs
(3GdfSNI eYGQVIs
(3HBNQgG bQGAI SfI (B365 (3hHChdgG efGhdI SfI (B425 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B318s
Keywords: (3GdJGQjNs